Science and biomarkers of vascular contributions to cognitive impairment and dementia (VCID): Methodologic development and advancements in clinical trials targeting vascular cognitive impairment and dementia (VCID). (7th December 2020) - Corriveau, Roderick A.
Abstract: Background: The scientific framework of vascular contributions to cognitive impairment and dementia (VCID) was introduced in 2013 in response to the fact that most individuals diagnosed with Alzheimer's dementia also have cerebrovascular pathology. The science of VCID brings into focus the hypothesis that vascular lesions may be a cause of cognitive impairment and dementia that occurs independently or, much more frequently, in the absence of a vascular diagnosis and in combination with one or more other brain pathologies. Method: The scope of VCID research is defined as the aging neurovascular unit integrating, and failing to cope with, biological insults due to vascular disease, proteinopathy including Alzheimer's pathology, metabolic disease, and immune activity. Moreover, the direct role of each pathology, and other co‐morbidities, in causing dementia is the subject of hypotheses that must be rigorously tested to move toward successful interventions. Result: In addition to better mechanistic and clinical understanding of VCID, which will result in targets, rigorously validated clinical trial ready VCID biomarkers have emerged as a critical priority for addressing the burden of dementia worldwide. Barriers include leveraging traditional research measures into bona fide clinical trial ready biomarkers, determining whether risk measures can provide sufficiently robust signals to serve as a valuable clinical biomarkers, and ensuring that VCID biomarkers that move forward are valid and useful for clinical trials and interventions across diverse populations as well as in populations that experience health disparities. Large scale efforts are underway to meet these goals to provide VCID biomarkers to promote effective clinical trial engagement in VCID. Conclusion: Because of the proven ability to prevent and treat cardiovascular disease and hypertension with population benefits for heart and stroke outcomes, it has now been proposed by many that understanding and targeting the biological mechanisms of VCID can have a similarly positive impact on public health. The development of VCID biomarkers is of critical importance in realizing this potential.